The Influence Of Growth, Firm Size, And Profitability On Carbon Emission Disclosure (Empirical Study Of Industrial Sector Manufacturing Companies Listed On The Indonesia Stock Exchange In 2019 - 2022) - Gardenia Try Puspitaningtyas; Dyah Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate and demonstrate how growth, firm size, and profitability influence the disclosure of carbonemissions among manufacturing companies in the industrial sector listed on the Indonesia Stock Exchange from 2019 to 2022. It employs a quantitative research approach, utilizing secondary data sourced from the annual reports and sustainability reports of these companies. The study's population comprises manufacturing companies in the industrial sector listed on the Indonesia StockExchange during the specified period. Purposive sampling was utilized to select a sample of 10 companies. The findings indicatethat both growth and firm size have a significant impact on carbon emission disclosure, whereas profitability does not demonstrate a similar effect.